2010
DOI: 10.1080/16506070903571014
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Coital Behaviour in Women Treated with Cognitive Behaviour Therapy for Superficial Coital Pain and Vaginismus

Abstract: The purpose of the present study was to investigate long-term coital behaviour in women treated with cognitive behaviour therapy (CBT) for superficial coital pain and vaginismus. Data were taken from a questionnaire concerning long-term coital behaviour sent to 59 women who presented to Linköping University Hospital because of superficial coital pain, had been diagnosed with vaginismus, and had been treated with CBT. Data were also traced from therapy records: mean follow-up time was 39 months, the women had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 18 publications
0
23
0
2
Order By: Relevance
“…These improvements in pain and sexual functioning for women receiving CBT were maintained at 6-month and 2.5-year follow-ups [96]. In a retrospective, uncontrolled follow-up study of women treated with CBT for superficial coital pain and vaginismus, 56 % of women reported a reduction in coital pain problems, but also reported having a greater sense of self as a sex partner and as a woman following treatment [111], thus highlighting the potential to see improvements in areas beyond the pain itself. To distinguish active psychotherapeutic properties from supportive effects of therapeutic interventions, a randomized trial examining the efficacy of individual CBT for vulvodynia compared to a supportive psychotherapy demonstrated that CBT resulted in significantly greater improvement in pain severity and sexual function between pre-and post-treatment, with gains being maintained at 1-year followup [112].…”
Section: Psychosocial Treatmentsmentioning
confidence: 73%
“…These improvements in pain and sexual functioning for women receiving CBT were maintained at 6-month and 2.5-year follow-ups [96]. In a retrospective, uncontrolled follow-up study of women treated with CBT for superficial coital pain and vaginismus, 56 % of women reported a reduction in coital pain problems, but also reported having a greater sense of self as a sex partner and as a woman following treatment [111], thus highlighting the potential to see improvements in areas beyond the pain itself. To distinguish active psychotherapeutic properties from supportive effects of therapeutic interventions, a randomized trial examining the efficacy of individual CBT for vulvodynia compared to a supportive psychotherapy demonstrated that CBT resulted in significantly greater improvement in pain severity and sexual function between pre-and post-treatment, with gains being maintained at 1-year followup [112].…”
Section: Psychosocial Treatmentsmentioning
confidence: 73%
“…Interestingly, most of the helpful interventions were components of sex therapy and psychological interventions (sex education, sensate focus exercises, talking about the meaning of vaginal penetration problem, relaxation training, and vaginal dilatation). A number of treatment studies have reported the use of informative and educational elements and behavioral exercises to treatment either as a stand‐alone intervention [26–28] or in combination with physiological treatments [9,29]. The results of this study suggest that psychological and sex therapy interventions are important components of a multidisciplinary approach to the treatment of vaginal penetration difficulties [25,30,31].…”
Section: Discussionmentioning
confidence: 80%
“…Both studies found that nearly half of the women could resume pain-free or close to pain-free intercourse following this first-line treatment. One recent retrospective long-term follow-up study investigated the effectiveness of CBT for women with combined superficial coital pain and vaginismus [153]. With a mean of 14 therapy sessions and an average follow-up time of 39 months, 81% of women who completed the evaluation questionnaire reported being able to have intercourse following treatment, while 61% rated their ability to have pain-free intercourse as at least 6 out of 10 (total ability to have intercourse without pain), and 61% rated their ability to enjoy intercourse as at least 6 out of 10 (total ability to enjoy intercourse).…”
Section: Combined Pvd and Vaginismusmentioning
confidence: 99%